GIGAQUIT RUM a project feasibility study - Lerio, Lourberto S.; Primicias, Jose Jesus Y. (Diliman, Quezon City College of Engineering, 1996)
The production of the distilled spirit, Gigaquit Rum would etched a mark in the world of distilled spirit. This is a Filipino product. It is manufactured at Bad-as, Placer, Surigao del Norte from where it is transported to its main customers. The site was primarily chosen after considering several factors, namely, environmental conditions, proximity to suppliers and customers, land size, transport and the lot purchase price. The project is poised to begin plant and equipment installations by the end of 1996 and operation will start on the following year. On 1998, It will be the launching of the product after being aged for a year. Market feasibility findings reveal a ready market for the product. Its market share is adopted from the smallest market share in the present market. Its target market is composed of the population whose age ranges from 18 to 69 years and belongs to class C and below. The initial demand of the product is 78,703 bottles in 1998 at it will experience an upward linear trend coping up with the increasing demand of distilled spirits. Technical feasibility shows a very high opportunity for the product in terms of technology, manpower, materials and machine. The process involved in producing the product is dependent upon the equipment which are easily operated. Raw materials came from local sources and the company bought one hectare of swamp land to accommodate demand. All equipment are also readily available. The total initial project cost is P2,708,459. In the financial feasibility, the initial funding required is estimated to be P2.8 million. P500,000 will come from the owners, the proponents of the project and the rest will loaned through Development Bank of the Philippines, Surigao City at 15% interest rates to be paid and compounded quarterly. The loan will be paid after ten years. In the first five years of operation, the project is operating profitably and all its measures for financial analysis and sensibility analysis favored the acceptance of the project. The internal rate of return is 16.20% which is above the MARR that is 15% that implies the project to be profitable. The return of investments is on the third year and seven and a half months of operation though its first year of operation generates no revenue. The net Income is increasing with respect to time and this increasing trend would eventually attract more investors. In terms of the socio-economic profitability, the project will have positive gains to its environment and to the government and its people. Partnership is the form of ownership adopted since it best suited a small scale project with nine personnel. Definitely, the project's product is one of a kind and something a Filipino would be proud of.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management.
Keywords: Rum industry; Rum; Participatory monitoring and evaluation (Project management)